2015
DOI: 10.1109/tuffc.2015.007016
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive thrombolysis using histotripsy beyond the intrinsic threshold (microtripsy)

Abstract: Histotripsy has been investigated as a non-invasive, drug-free, image-guided thrombolysis method that fractionates blood clots using acoustic cavitation alone. In previous histotripsy-mediated thrombolysis studies, cavitation clouds were generated using multi-cycle pulses and tended to form on vessel wall. To avoid potential cavitational damage to vessel wall, a new histotripsy approach, termed Microtripsy, has been recently discovered where cavitation is generated via an intrinsic-threshold mechanism using si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…In another study, a threshold of −33 MPa was observed in water by a focused acoustic pulse, and it was considered that cavitation bubbles were originated from nanometer-sized nuclei [42]. In histotripsy, cavitation bubbles are induced by extremely high-intensity pulses with a peak-negative pressure exceeding the threshold range and a soft tissue is eroded by the collapse of the bubbles [43][44][45]. Although the intrinsic threshold is extremely high, an acoustic pulse with a longer duration can generate clouds of bubbles even at a lower intensity because of the mechanism called "shock scattering" [46].…”
Section: Trigger Hifu Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a threshold of −33 MPa was observed in water by a focused acoustic pulse, and it was considered that cavitation bubbles were originated from nanometer-sized nuclei [42]. In histotripsy, cavitation bubbles are induced by extremely high-intensity pulses with a peak-negative pressure exceeding the threshold range and a soft tissue is eroded by the collapse of the bubbles [43][44][45]. Although the intrinsic threshold is extremely high, an acoustic pulse with a longer duration can generate clouds of bubbles even at a lower intensity because of the mechanism called "shock scattering" [46].…”
Section: Trigger Hifu Sequencementioning
confidence: 99%
“…The typical duration of the trigger pulse was 10-100 µs. The duration time was set longer than the pulse duration of several µs in histotripsy studies [40,41,[43][44][45]. Since a peak negative pressure of a typical trigger pulse did not exceed the intrinsic threshold, typically around −30 MPa, the relatively longer duration time was necessary to form bubble clouds through a shock scattering mechanism.…”
Section: Trigger Hifu Sequencementioning
confidence: 99%
“…In addition, ultrasound combined with microbubble contrast agents has been demonstrated to successfully augment clot dissolution in the presence or absence of thrombolytic drugs [1820]. Ultrasound has also been investigated as an independent thrombolysis method under approaches utilizing acoustic cavitation [2126]. …”
Section: Introductionmentioning
confidence: 99%
“…Using the shock scattering approach, the cavitation cloud is less-confined and tends to be generated in contact with vessel wall where the weak nuclei reside, resulting in potential vessel damage from histotripsy treatment. A new histotripsy approach, termed microtripsy, has been recently investigated for thrombolysis application to improve treatment precision and avoid potential vessel damage [26]. Microtripsy uses an intrinsic threshold mechanism where a cavitation cloud is initiated via a single ultrasound pulse with only one high negative pressure phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation